Government and Conflict Handling of Free Papua Organizations in Human Rights Approach - Raditya Feda Rifandhana; Bambang Angkoso Wahyono; Suardi Suardi; Ivan Prasetyo; Gerin Mayrantika Tengor; Yosef Rayrego (Universitas of Muhammadiyah Makassar, 2024)
Since 1963 there has been a conflict between Papua and Indonesia called the OPM conflict, at first Papua wanted to secede with Indonesia, in the conflict between Papua and Indonesia originating from the New York Agreement became a controversy, Indonesia until now is busy handling conflicts in Papua, handling the Papua conflict that never ends peacefully, so there are casualties not only from civilians, even from the TNI-POLRI, the purpose of this study is to prioritize the handling of OPM conflicts with a humanist approach to handling the case of independent Papua, the Research Method is a Normative Juridical Research Method, that this research conducts research by means of a research approach through laws and regulations and Legal Theory relevant to this study, the formulation of the problem used is how the role of the government in handling OPM conflicts in Papua in human rights perspective, as well as obstacles in handling OPM conflict?, in the findings of this study, that seeing from the reality that the existence of OPM can dilute the love of the homeland for Indonesia, even the casualties due to the OPM conflict with Indonesia, in conclusion the government and humanist human rights approach in handling the case of the Free Papua Organization